Evaluation of the vibration influence on the workers in casthouses - A. M. Lazarenkov; S. A. Horeva; T. A. Tavgenj (Литьë и металлургия)
There are given the results of investigations of the levels of vibrations at the working places of founders and there is given the evaluation of vibration on the professional disease of the workers.